PELAKSANAAN PERJANJIAN KREDIT PT. BANK RAKYAT INDONESIA (PERSERO) UNIT BUKIT AGUNG CABANG PANGKALAN KERINCI DENGAN JAMINAN SURAT KETERANGAN GANTI RUGI (SKGR) - Artika, Primata Prischa; Bachtiar, Maryati; ', Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Function Bank is one of them as a deposit-taking institution and channeling funds to the community through loans to communities in need . Banks should conduct a careful assessment of the character , capacity, capital , collateral and business prospects of the debtors . The people's choice for financial institutions due to the need for prompt delivery , no complicated procedures , and requirements are easily met. PT Bank Rakyat Indonesia ( Persero ) will continue to develop new forms of services for micro and small businesses in the form of direct financing .In the implementation of this credit will always be associated with the collateral issue. Although the provision of credit to guarantee the ground by a certificate of indemnity ( SKGR ) still caused problems, but financial institutions PT Bank Rakyat Indonesia ( Persero ) Unit Mount Agung Branch Pangkalan Kerinci , has undertaken the provision of credit to guarantee indemnity certificate . in this case certainly PT Bank Rakyat Indonesia ( Persero ) Unit Mount Agung Branch Pangkalan Kerinci is already thinking about the risks that arise in case of bad credit and procedures for the settlement of the guarantee .